Taxonomic and phylogenetic reassessment of a large-bodied dinosaur from the earliest dinosaur-bearing beds (Carnian, Upper Triassic) from southern Brazil. (2nd January 2021) - Garcia, Maurício S.; Müller, Rodrigo T.; Pretto, Flávio A.; Da-Rosa, Átila A. S.; Dias-Da-Silva, Sérgio
Abstract : Upper Triassic (Carnian) strata from the Candelária Sequence of southern Brazil bear the oldest records of dinosaurs worldwide. In consequence, investigation of the specimens yielded by these fossiliferous units is crucial for a more comprehensive knowledge regarding the origin, early diversification and radiation of dinosaurs. Herein we reassess a dinosaur specimen from Brazil, informally known as the 'Big Saturnalia ', a supposed large-sized sauropodomorph unearthed at the 'Cerro da Alemoa' locality in Santa Maria municipality, Rio Grande do Sul State. However, our phylogenetic analyses and comparisons of the known elements of this specimen resulted in herrerasaurid affinities instead. In fact, it is the largest specimen so far of a herrerasaurid from the Candelária Sequence. It preserves cranial and postcranial elements, with the former being unprecedented for dinosaurs from the Alemoa local fauna. The morphology of the specimen allows new insights into the anatomy, evolution and distribution of some character states among Herrerasauridae, including but not limited to the typical craniocaudally short caudal dorsal vertebrae. Moreover, the specimen adds to the dinosauromorph diversity in the Carnian units of southern Brazil and its large size provides further support for herrerasaurids as top-tier predators during the dawn of dinosaurs in south-western Pangaea.